Physicochemical, antioxidant and antimicrobial properties of mechanically deboned chicken meat protein films enriched with various essential oils - Sarıcaoğlu, Furkan Türker; Turhan, Sadettin (Elsevier, 2020)
Thyme, rosemary or clove essential oils at 1.5 % were added to mechanically deboned chicken meat protein (MDCM-P) films, and physicochemical, antioxidant and antimicrobial properties were investigated. Moisture, thickness, and opacity increased, whereas solubility and water vapor permeability decreased with addition of essential oil. The tensile strength of films decreased with essential oil incorporation, while the elongation at break values increased for rosemary and clove essential oil enrichment. Films containing clove essential oil had the lowest roughness value which caused the lowest water vapor permeability. Antioxidant and antimicrobial properties were significantly improved with essential oils, and films containing clove essential oil exhibited the highest activity. It can be concluded that the physicochemical, antioxidant and antimicrobial properties of MDCM-P films could be improved with essential oils and clove essential oil could be the best option when compared with others.
Keywords: Mechanically deboned meat protein; Edible films; Essential oil; Microstructure; Antimicrobial activity